Структурний аналіз надійності сільськогосподарської техніки при експлуатації на біопально-мастильних матеріалах - Журавель, Дмитро Павлович; Бондар, Андрій Миколайович; Філенко, Д. Ю.; Zhuravel, Dmytro; Bondar, Andrii; Filenko, D. (Запоріжжя : ТДАТУ, 2022)
UA: В роботі розглянуто сільськогосподарську техніку як складну багатоопераційну систему. Складено граф стану сільськогосподарської техніки в період її експлуатації та визначено значення ймовірності знаходження в кожному з станів. Виявлено агрегати, через яких виникає найбільша ймовірність знаходження сільськогосподарської техніки в стані ремонту. В період експлуатації в межах заданого ресурсу розмічений граф не має тупикових станів, а ймовірності переходів сільськогосподарської техніки з одного в інше стабілізується в області фінальних своїх значень, які характеризують рівень надійності окремих агрегатів. Для зменшення кількості відмов необхідно провести комплекс заходів для адаптації сільськогосподарської техніки при експлуатації на біопально- мастильних матеріалах. EN: The paper considers agricultural machinery as a complex multi - operational system. The limited volume and contradictory results of research in the field of replacement of petroleum fuels with biological ones do not allow to unambiguously judge the impact of biofuel composition on energy, fuel and economic, environmental and other indicators that form the technical level of agricultural machinery. The available published incomplete statistics on the level of reliability of different types of operated machines and systems at present due to the intensive development of production do not fully reflect the actual state of the problem, especially against the background of the use of alternative fuels and lubricants of biological origin. Аnalysis of the system in numerical form, the results of own operational researches, and also expert estimations of experts in repair and service of agricultural machinery were used. Graphs of the state of agricultural machinery during its operation are made and the value of the probability of being in each of the states is determined. Units were identified, due to which there is the greatest probability of agricultural machinery being in a state of repair. During the period of operation within the given resource the marked graph has no deadlocks, and the probability of transitions of agricultural machinery from one to another is stabilized in the area of its final values, which characterize the level of reliability of individual units. The characteristics of failures of units and systems of agricultural machinery during operation on biofuel and lubricants indicate significant indicators of the number of failures by groups of complexity. To reduce the number of failures, it is necessary to carry out a set of measures for the adaptation of agricultural machinery during operation on biofuels and lubricants.
Structural analysis of the reliability of agricultural machinery in operation on biography and lubricants
Журавель Д. П., Бондар А. М., Філенко Д. Ю. Структурний аналіз надійності сільськогосподарської техніки при експлуатації на біопально-мастильних матеріалах. Науковий вісник Таврійського державного агротехнологічного університету : електронне наукове фахове видання. Запоріжжя : ТДАТУ, 2022. Вип. 12. том 3. C. 42-53.
Keywords: біопально-мастильні матеріали; моделювання надійності; сільськогосподарська техніка; діагностування; ймовірність відмови; граф стану; структурний аналіз; прогнозування ресурсу; biofuels; reliability modeling; agricultural machinery; diagnostics; failure probability; state graph; structural analysis; resource forecasting